The Effect of Compensation and Work Discipline on Employee Performance at Hotel Plaza Inn Kendari - Sahyunu, Sahyunu; Titop , Herman Titop; Muslimin, Muslimin; Asri Djauhar , Asri Djauhar; Imran, Imran; Pratiwi , Anggy Pratiwi (International Journal of Management and Education in Human Development, 2022)
This study aims to determine the effect of compensation and work discipline on employee performance at the Plaza Inn Kendari hotel. The data collection technique was used by distributing questionnaires to respondents who are employees of the Plaza Inn Kendari hotel. The number of respondents in this study amounted to 76 people. The respondents were selected using a saturated sampling technique or using the entire population as the research sample. The data from the questionnaire collection was then carried out quantitative analysis including validity test, reliability test, multiple linear regression analysis, and hypothesis testing through t-test and F test. Based on multiple linear regression analysis shows that compensation and work discipline have a positive effect on employee performance with a calculated F value F - count 78.006 > F - table 3.12 and a significant value 0.000 <0.05. Compensation has a partial positive effect on employee performance with a value of t - count 10.737 > t - table 1.993 and a significant value of 0.000 <0.05. Work discipline has a partially positive effect on employee performance with a value of t - count 6.682 > t - table 1.993 and a significant value of 0.000 <0.05. So that the proposed hypothesis can be accepted.